2013
DOI: 10.1093/neuonc/not082
|View full text |Cite
|
Sign up to set email alerts
|

Increase in tumor-associated macrophages after antiangiogenic therapy is associated with poor survival among patients with recurrent glioblastoma

Abstract: Antiangiogenic therapy is associated with increased radiographic responses in glioblastomas, but tumors invariably recur. Because tumor-associated macrophages have been shown to mediate escape from antiangiogenic therapy in preclinical models, we examined the role of macrophages in patients with recurrent glioblastoma. We compared autopsy brain specimens from 20 patients with recurrent glioblastoma who received antiangiogenic treatment and chemoradiation with 8 patients who received chemotherapy and/or radioth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
183
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(192 citation statements)
references
References 32 publications
8
183
1
Order By: Relevance
“…Inflammatory factors have been linked with resistance to anti-VEGF therapy in multiple studies in glioblastoma (10,38). Here, we detected increases in multiple cytokines in circulation during and after cediranib with chemoradiation, which were concomitant with plasma elevations in the hypoxia marker CAIX.…”
Section: Discussionmentioning
confidence: 68%
“…Inflammatory factors have been linked with resistance to anti-VEGF therapy in multiple studies in glioblastoma (10,38). Here, we detected increases in multiple cytokines in circulation during and after cediranib with chemoradiation, which were concomitant with plasma elevations in the hypoxia marker CAIX.…”
Section: Discussionmentioning
confidence: 68%
“…We previously have shown that anti-VEGF therapy can enhance the recruitment of TAMs in preclinical GBM models and that the number of TAMs is negatively correlated with survival in GBM patients, confirming their potential as a therapeutic target in GBM (11,68). A recent preclinical study in GBM found that survival could be enhanced by shifting the TAM phenotype away from an M2-like phenotype (33).…”
Section: Discussionmentioning
confidence: 84%
“…The two extremes of the phenotypic spectrum of TAMs are defined as the alternatively activated protumor (M2) versus classically activated antitumor (M1) states (23)(24)(25). We previously have shown that the degree of TAM infiltration in GBM patients treated with anti-VEGF therapy is inversely correlated with survival (26). These data point to the role of TAMs as potential mediators of resistance to anti-VEGF therapy in GBM.…”
Section: Significancementioning
confidence: 95%